The Novelty of Religion and Art: Should We Combine with STEM Education? - Husni Mubarok; Nur Shabrina Safitri; Alif Syaiful Adam (Studies in Philosophy of Science and Education, 2020)
One of the meaningful learning implications is the formation of Long-Term Memory (LTM). Through the development of concepts related to the problems of everyday life that bridge LTM and the implementation of Science, Technology, Engineering and Mathematics (STEM) as an educational approach, it enables students to realize the importance of knowledge for society. However, some aspects of society are excluded from STEM, in that way a transformation needs to be carried out. Art and Religion need to be developed in STEM to nurture students, environment, and society to the full. Several examples are presented to represent the relationship between STEM with art and religion, not only in terms of learning outcomes in schools, but also the expectations to create resilient people in facing the future challenges. With Science, Technology, Religion, Engineering, Art, and Mathematics (STREAM) education approach.